(untitled) (Annals of Medical Research, 2021)
Aim: Pes Planus (PP) was defined as the decrease or loss of length of arcus longitudinalis medialis (MLA). The aim of the present study is to find out whether PP causes any anthropometric changes in individuals and to determine the relationship between PP and foot type.Materials and Methods: A total of 100 individuals, 50 PP patients (25 female and 25 male) and 50 healthy individuals (25 female and 25 male), between the ages of 11 and 14 were included. Circumference of waist, hip, thigh, leg, bimalleolar and foot; tarsal and MLA height; bimalleolar and foot breadth were measured. Leg index, foot index and foot types were calculated with various anthropometric rates. Results: Significant differences were found in female circumference measurements of the waist, hip, both thighs and right foot bimalleolar (P .05). Significant differences were found in right and left foot bimalleolar circumferences measurements and leg indexes in men (P .05). Significant differences were found in both genders in right and left foot MLA and tarsal heights (P .05).Conclusion: It was found that PP affects not only the foot anthropometric measurements but also the hip, thigh and leg measurements. Early treatment for PP can provide irreversible lower extremity problems that cause lower quality of life.